Clinical isolates of Mycobacterium tuberculosis differ in their ability to induce respiratory burst and apoptosis in neutrophils as a possible mechanism of immune escape - Romero, María Mercedes (2012)
Fil: Romero, María Mercedes. Academia Nacional de Medicina. Instituto de Medicina Experimental; Argentina.